Joseph Smith, Jesus, and Satanic opposition atonement, evil and the Mormon vision - Davies, Douglas James (Farnham, Surrey, England ; Burlingtion, VT : Ashgate, 2010)
Explores Mormon theology in new ways from a scholarly non-Mormon perspective. Bringing Jesus and Satan into relationship with Joseph Smith, Davies shows how the Mormon "Plan of Salvation" can be equated with mainstream Christianity's doctrine of the Trinity as a driving force of the faith. Davies shows how renewed Mormon interest in theological questons of belief can be understood against the background of Mormon church organization and its growing presence on the world-stage of Christianity.
Jesus in early Mormon America -- Mormon-Israel -- Millennial kingdom experiment -- Plan and trinity -- Jesus, the living and the dead -- Joseph, Jesus and Lucifer -- Atonement -- Jesus, Satan and evil -- Jesus and doctrinal kinship -- The hope of glory -- Jesus and the Holy Ghost -- Jesus, opposition, otherness and sacrifice.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Jesus Christ -- Mormon interpretations; Church of Jesus Christ of Latter-day Saints -- Doctrines; Mormon Church -- Doctrines; RELIGION / Christian Theology / Christology; Electronic books